2021
DOI: 10.3390/polym13101536
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Anionic Azo Dye New Coccine Using Silica and Silica-gel with Surface Modification by Polycation

Abstract: In the present work, adsorption of anionic azo dye, new coccine (NCC) on silica and silica-gel in an aquatic environment was discovered. Effective conditions such as adsorption time, pH, the influence of dosage on NCC adsorption using strong polycation, poly-diallyl-dimethylammonium chloride (PDADMAC) modified silica (PMS) and PDADMAC modified silica-gel (PMSG) were systematically studied. The removal of NCC using PMS and PMSG were much higher than that using raw silica and silica-gel without PDADMAC in all pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Also, during the adsorption of reactive wool dyes, Gemeay et al (2020) reported the role of the sulfonate and oxygenated groups for enhanced hydrogen bonds and electrostatic interaction. Pham et al (2021) synthesized a silica-based adsorbent with a high positive surface charge via functionalization with poly-diallyl-dimethylammonium chloride. Based on the study, efficient dye uptake was achieved following a complex formation between the oxygen atoms on the sulfonic group of the azo dye and the adsorbents' amine groups.…”
Section: Silicamentioning
confidence: 99%
“…Also, during the adsorption of reactive wool dyes, Gemeay et al (2020) reported the role of the sulfonate and oxygenated groups for enhanced hydrogen bonds and electrostatic interaction. Pham et al (2021) synthesized a silica-based adsorbent with a high positive surface charge via functionalization with poly-diallyl-dimethylammonium chloride. Based on the study, efficient dye uptake was achieved following a complex formation between the oxygen atoms on the sulfonic group of the azo dye and the adsorbents' amine groups.…”
Section: Silicamentioning
confidence: 99%
“…The first PAMAM-grafted adsorbents for heavy metal ions were proposed with silica gel as the substrate [ 43 ]. Silica gel is one of the most widely used adsorbent matrix materials because of its good thermal stability, superior mechanical resistance, modifiability, and high surface area [ 44 , 45 , 46 ]. Qu et al prepared a series of ester- and amino-terminated PAMAM-grafted silica gels (SiO 2 -G0-SiO 2 -G4.0) by a divergent method.…”
Section: Adsorbents Of Different Substratesmentioning
confidence: 99%
“…Each adsorbent has its own characteristics, such as porosity, pore structure, adsorbent surface area, and structural specificity [124]. A high range of adsorbents have been studied to remediate dye contaminated waters: clays [125][126][127], chitosan [128,129], cyclodextrin [130][131][132], eggshell [51,[133][134][135], orange peel [136], fluorene-based covalent triazine framework [137], cellulose [138], wool [139], shrimp [140], rice bran hydrogel beads [141], coccine [142], seeds [143,144].…”
Section: Possible Adsorbentsmentioning
confidence: 99%